Tailored for China: did it work? Reflections on an intensive study abroad programme for Chinese student teachers. Issue 7 (3rd October 2019) - Wang, Fang; Clarke, Anthony; Webb, Andrea S
ABSTRACT: This study examines how a cohort of 32 Chinese student teachers experience a 3-week Intensive Study Abroad Programme in Canada, which focused on facilitating understanding of teaching and learning from an international perspective. Research findings underscore the effectiveness of a context responsive approach to cross-cultural teaching and learning that places emphasis upon modelling and deliberate explication of teaching practice, experiential learning and dialogic reflection.